Pelatihan Pembuatan Parem dan Minuman Herbal Sebagai Peningkat Imunitas dan Peluang Usaha Mandiri - Siti Uswatun Hasanah; Diki Prayugo Wibowo; Hesti Riasari; Sani Nurlaela (Ilin Institute, 2023)
Conditions after the COVD-19 pandemic still require residents to maintain their immunity, one of which is by using family medicinal plants. Ginger plant is a traditional spice that is found in many areas. This community service activity aims to provide knowledge about the benefits of herbal plants as immune boosters and processing ginger spices to become herbal drink products and parem, as daily consumption. The method of activity is to provide counseling to residents and make products directly, along with packaging and brochures as product companions. As a result of community service activities, people get additional knowledge about herbal plants that can increase body immunity as well as get knowledge about simple ways to process herbal plants.